2007
DOI: 10.1002/ijc.23021
|View full text |Cite
|
Sign up to set email alerts
|

Risk of lung cancer following exposure to carbon black, titanium dioxide and talc: Results from two case–control studies in Montreal

Abstract: (IARC) recently evaluated the carcinogenicity of three poorly soluble weakly-toxic substances: carbon black, titanium dioxide and talc. Though there is evidence of carcinogenity in experimental animals for these substances, the evidence in humans is sparse and equivocal. In the context of two large population based case-control studies of lung cancer carried out in Montreal, we were able to study the possible relationships between the exposure to each of these substances and subsequent risk of lung cancer. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 44 publications
0
39
0
1
Order By: Relevance
“…In Study II, controls were recruited according to the distributions of age, sex, and area of residence of lung cancer cases. Details of subject ascertainment and data collection have been presented in detail previously [Siemiatycki and Richardson, 1991;Ramanakumar et al, 2006Ramanakumar et al, , 2008.…”
Section: Methodsmentioning
confidence: 99%
“…In Study II, controls were recruited according to the distributions of age, sex, and area of residence of lung cancer cases. Details of subject ascertainment and data collection have been presented in detail previously [Siemiatycki and Richardson, 1991;Ramanakumar et al, 2006Ramanakumar et al, , 2008.…”
Section: Methodsmentioning
confidence: 99%
“…Although limited epidemiological studies in U.S. and European TNP production factories showed no significant respiratory carcinogenic risks [11][12][13][14]. TNP toxicity has been observed in diverse models, such as rodents [15][16][17][18], aquatic organisms [19][20][21], and human cells [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that a carbon black counter electrode could achieve a PCE of 8.29%, close to the value produced by a DSSC with a platinum counter electrode: a PCE of 8.35% (Wu et al, 2016). The use of carbon black, however, should be avoided due to its possible carcinogenic effect on humans (Ramanakumar et al, 2008).…”
Section: Introductionmentioning
confidence: 87%